(untitled) (Journal of Engineering, 2014)
In this research an analysis for improving the fatigue behavior (safety factor of fatigue) of non- articular prosthetic foot (SACH) in the region (Bolt Adapter).The laser peening was carried to the fatigue specimens to improving the fatigue properties of bolt’s material. The tests of mechanical properties and fatigue behavior were carried for material that the bolt manufacture from it, a region where the failure occur and inserted of these properties to the program of engineering analysis (Ansys) to calculate the safety factor of fatigue. The results showed that the safety factor after hardening by laser is increased by 42.8%.